PRAISE ME! How Iceland's dailies report on New York Times articles about Iceland - Anna Andersen 1986- (2015)
The aim of this research project was to investigate Icelanders’ reactions to how they are portrayed by the outside world, specifically through the Icelandic media’s coverage of New York Times articles featuring Iceland. Of the roughly 3,000 articles mentioning the words “Iceland” or “Icelandic” retrieved from the New York Times over a ten-year period, from 2004 through 2013, it was determined that 445 articles specifically featured an Icelandic person, place or entity. Those articles were analyzed by category and subject. Then, the rate at which Iceland’s main dailies, Morgunblaðið or Fréttablaðið, covered them was determined and the coverage was analyzed. Finally, to provide perspective, similar analysis was conducted on the content of Malta’s comparable dailies. The main results showed that Iceland’s dailies picked up significantly more articles about Iceland in the New York Times than the Maltese media picked up about Malta. There was also a notable difference in the way that the country’s dailies framed their coverage. Whereas the Maltese media tended to use New York Times articles about Malta as a source for their version of the news featured in the New York Times story, the Icelandic media tended to view New York Times articles about Iceland as newsworthy events in and of themselves, with roughly half of the headlines emphasizing the fact that The New York Times had praised or simply paid attention to Iceland. Thus the Icelandic media betrays the nation’s preoccupation with being in the spotlight and its need for external validation, which is not true of the media in all small island nations. Markmið þessa rannsóknarverkefnis var að rannsaka viðbrögð Íslendinga við því hvernig umheimurinn fjallar um þá, nánar tiltekið með því að grannskoða fréttir Fréttablaðsins og Morgunblaðsins um Íslandstengda umfjöllun dagblaðsins New York Times. Rannsóknin leiddi í ljós að af þeim rúmlega 3.000 greinum sem innihéldu orðin „Iceland“ eða „Icelandic“ sem birtust í New York Times á tíu ára tímabili, frá 2004 og út árið ...